2000
DOI: 10.1021/ja000128g
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Tandem Pseudoproline Ligations of Proline-Rich Helical Peptides

Abstract: We have developed a bidirectional ligation strategy for preparing proline-rich peptides that couples three unprotected segments in tandem to form two pseudoproline bonds (thia-or oxaproline) without the need for a protection scheme. Ligation in the CfN direction exploits the regioselectivity of an amino terminal (NT)-Cys in forming a thiaproline bond over an NT-Ser or NT-Thr peptide in forming an oxaproline bond with a peptide that bears a carboxyl terminal (CT)-glycoaldehyde ester. Thus, successive ligations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…This reaction was applied in the assembly of proline-rich analogs of the 59-residue helical antibacterial peptide bactenecin 7, which showed comparable biological activities to the natural product [113]. In this aspect it is important to note that a three-segment condensation was used, in which the first junction was constructed by the formation of a thiazolidine of the Cys peptide -a faster step than the formation of the corresponding oxazolidine of the Thr peptide.…”
Section: Imine Ligations With Subsequent Pseudo-pro Formationmentioning
confidence: 99%
“…This reaction was applied in the assembly of proline-rich analogs of the 59-residue helical antibacterial peptide bactenecin 7, which showed comparable biological activities to the natural product [113]. In this aspect it is important to note that a three-segment condensation was used, in which the first junction was constructed by the formation of a thiazolidine of the Cys peptide -a faster step than the formation of the corresponding oxazolidine of the Thr peptide.…”
Section: Imine Ligations With Subsequent Pseudo-pro Formationmentioning
confidence: 99%
“…The O,N-acyl transfer reaction provides a proline mimetic that retains the amide backbone structure of an α-peptide. In contrast to thiaproline ligation [13][14][15] which is usually performed in aqueous buffers at pH 4 to 7, oxaproline ligation was performed under nearly nonaqueous conditions containing pyridine and acetic acid [14,21,42]. It was also shown that NT-amino acids such as NT-Cys, NTTrp, and NT-His can be ligated under such a condition [34].…”
Section: C-to-n Tandem Ligationmentioning
confidence: 99%
“…Even before the mechanism of protein splicing was fully elucidated [10], proximity-driven ligation methods had been developed for ligating unprotected peptide segments [11][12][13][14][15]. For our purpose, we call the unassisted ligation reaction orthogonal ligation because its mechanism in forming an amide bond involves a specific N-terminal (NT) amino acid that is generally orthogonal to other NT-amino acids [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations